Build Early Childhood Mathematical Logic Intelligence (AUD) with ScaffoldingAt the Beam Center at the Al-Falah School, Ciracas, East Jakarta - Zukhairina Zukhairina; Sri Hidayati; Rita Zubaidah; Schunk Yingxiang (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2022)
the purpose of this research is to describe the experience of Al-Falah school in Jakarta in building mathematical logic intelligence through beam centers using scaffolding. The research was conducted using a qualitative descriptive research approach, this is intended to be able to reveal empirical facts in a natural way, and to reveal something behind every event (some things beyond) in building mathematical logic intelligence, and throughout a series of learning activities for Early Childhood Education in Indonesia. Al-Falah school in a more focused and in-depth manner. The findings of the study stated that the use of scaffolding by teachers during the learning process at the beam center strongly supports the development of children's mathematical logic, this is evidenced by the increasing stage of children's playing with blocks and how children can solve their own problems while playing.